2018
DOI: 10.30638/eemj.2018.090
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Oxidation Integrated Into Bioleaching of Pyrite and Chalcopyrite Using Immobilized Biomass

Abstract: Chemical oxidation of pyrite and chalcopyrite by ferric sulfate (Fe2(SO4)3) solution and biogenic ferric iron obtained by mixed culture of isolated thermotolerant Acidithiobacillus sp. 13Zn and Leptospirilum ferriphilum CC immobilized on natural carrierszeolite and shungite was studied. Oxidation rate of sulfide minerals was estimated by the decrease of Fe 3+ (oxidant) and increase of Fe 2+ ions in the solution. It was revealed that chemical oxidation of chalcopyrite by biogenic ferric iron occurred 2-3 times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Lei et al [16] employed microorganisms to bio-leach the raw tellurium-bismuth ore, and found that less than 80% of tellurium can be leached into lixivium. During the bio-leaching of sulfide, Fe 3+ plays an active and promoting role and Fe 2+ can be oxidized to Fe 3+ by bacteria [17][18][19][20]. However, the cultivation of microorganisms and the low production efficiency limit its application.…”
Section: Introductionmentioning
confidence: 99%
“…Lei et al [16] employed microorganisms to bio-leach the raw tellurium-bismuth ore, and found that less than 80% of tellurium can be leached into lixivium. During the bio-leaching of sulfide, Fe 3+ plays an active and promoting role and Fe 2+ can be oxidized to Fe 3+ by bacteria [17][18][19][20]. However, the cultivation of microorganisms and the low production efficiency limit its application.…”
Section: Introductionmentioning
confidence: 99%